Specific Lyt 123 cells are involved in protection against Listeria monocytogenes and in delayed-type hypersensitivity to listerial antigens (The Rockefeller University Press, 1979)
Specific anti-Lyt antisera and complement were used to determine the Lyt phenotype of peritoneal exudate T lymphocytes from Listeria monocytogenes-immune mice. It was found that Lyt 123+ T cells are crucially involved both in protection against listerial infection and in delayed-type hypersensitivity (DTH) to listerial antigens. Thus, both functions critically depend on a T-cell subclass phenotypically different from that which mediates DTH to noninfectious antigens and help in antibody formation on the one hand, as well as those T cells mediating cytotoxic reactions on the other.